2014
DOI: 10.1007/s00464-014-3636-1
|View full text |Cite
|
Sign up to set email alerts
|

Transanal versus traditional laparoscopic total mesorectal excision for rectal carcinoma

Abstract: Transanal TME appears associated with a significant higher rate of completeness of the mesorectum. Further studies are necessary to evaluate this novel technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 19 publications
6
155
1
11
Order By: Relevance
“…Although more studies are required to be confirmed the above findings, the comparative results published by Velthuis et al [7] , indicated that TaTME may be associated to a significantly higher rate of completeness of mesorectal excision, compared to laparoscopic TME.…”
Section: Oncological Outcomesmentioning
confidence: 74%
See 2 more Smart Citations
“…Although more studies are required to be confirmed the above findings, the comparative results published by Velthuis et al [7] , indicated that TaTME may be associated to a significantly higher rate of completeness of mesorectal excision, compared to laparoscopic TME.…”
Section: Oncological Outcomesmentioning
confidence: 74%
“…Results from four studies [7,11,12,115] , addressed positive CRM in 10 out of 136 patients (7.3%), while all studies, except two [103,113] , reported a mean number of retrieved lymphnodes equal to or greater to 12.…”
Section: Oncological Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative outcomes and oncological results of taTME and laTME were reported by several retrospective and comparative studies to be similar. Nevertheless, others have also reported specific intraoperative complications observed during taTME, such as urethral or bladder injury and rectal or vaginal perforation [11,12,13,14,29,30,31]. Despite that, in our first 25 cases with middle or lower third rectum cancer, we managed to avoid severe operative complications most likely due to previous training and very thorough preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a new kind of minimally invasive surgical procedure, i.e. transanal TME (taTME), has rapidly become of interest in minimally invasive surgery research [11,12,13,14]. Besides conventional laparoscopic surgery, taTME has been introduced in order to ease the technical aspects of mesorectal excision from the bottom towards the pelvis.…”
Section: Introductionmentioning
confidence: 99%